2022
DOI: 10.1530/eje-21-0850
|View full text |Cite
|
Sign up to set email alerts
|

Metformin maintains intrahepatic triglyceride content through increased hepatic de novo lipogenesis

Abstract: Objective: Metformin is a first-line pharmacotherapy in the treatment of type 2 diabetes, a condition closely associated with NAFLD. Although metformin promotes weight loss and improves insulin sensitivity, its effect on intrahepatic triglyceride (IHTG) remains unclear. We investigated the effect of metformin on IHTG, hepatic de novo lipogenesis (DNL) and fatty acid (FA) oxidation in vivo in humans. Design and Methods: Metabolic investigations, using stable-isotope tracers, were performed in 10 insulin-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…These findings were in accordance with earlier studies suggesting a beneficial lipid-lowering effect of metformin (Song et al, 2015;Choi et al, 2017;Zhu et al, 2018). In contrast, a recent report showed that metformin treatment improved weight loss and insulin resistance in humans without improvement in intrahepatic TG content, partly through increased hepatic fatty acids (FA) synthesis (Green et al, 2022). The discrepancy in findings with our results may due to dose and duration of metformin exposure or differential experimental condition such as diet structure.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were in accordance with earlier studies suggesting a beneficial lipid-lowering effect of metformin (Song et al, 2015;Choi et al, 2017;Zhu et al, 2018). In contrast, a recent report showed that metformin treatment improved weight loss and insulin resistance in humans without improvement in intrahepatic TG content, partly through increased hepatic fatty acids (FA) synthesis (Green et al, 2022). The discrepancy in findings with our results may due to dose and duration of metformin exposure or differential experimental condition such as diet structure.…”
Section: Discussionsupporting
confidence: 91%
“…Metformin also has a beneficial effect on the lipid profiles of patients with NAFLD, according to a previous trial, where 500 mg metformin administered for 4 months significantly decreased liver enzyme and triglyceride levels, and increased high-density lipoprotein (HDL)-cholesterol levels in patients (68). This is in line with another study which revealed that 500 mg metformin administered for 3 months decreased VLDL and triglyceride levels in 10 patients who were at a risk of developing NAFLD (69). Another study similarly reported that the daily administration of 850 mg metformin for 6 months reduced liver enzyme, total cholesterol and triglyceride levels, and increased HDL-cholesterol levels (70).…”
Section: Nafld For 6 Monthssupporting
confidence: 75%
“…As such, the effect of metformin administered in this model, with a hypercaloric diet, had not been explored. Despite the controversial effect of metformin in in vivo studies, some human studies suggested that metformin maintains the intrahepatic TG content [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%